Interfaz con transmisor de corriente en aplicación con dspic - Valdivieso A., Carlos (2009)
This project was implemented with the aim of showing the benefits of using DsPic in applications over long distances. In this case, a DsPic is used to control the temperature in a drying cabinet for Car Painting. The sensor signal is amplified and conditioned to go into the current transmitter as a voltage input. The help of a loop receiver is needed to transform the current signal in voltage. The current receiver has a conditioned output from 0-5 VDC that connects to an analog input of the DSPIC4011 microcontroller in order to read sensor’s data. This project makes use of Visual Basic to monitor the sensor’s signal using the RS232 serial port and the UART module from the DSPIC. The integrated circuit MAX3232 converts TTL signals from the DSPIC to RS232 level signals for the PC.